Isothiocyanates from Chorispora tenella and their toxicity to liver and thyroid cell lines - Arnold, Olivia, author; Ramsdell, Howard, advisor; Legare, Marie, committee member; Hanneman, William, committee member; Clements, William, committee member; Pillard, David, committee member (Colorado State University. Libraries, 2018)
Consumption of Brassica plants like Chorispora tenella that contain isothiocyanates can be detrimental to the health of livestock, specifically horses. Late term gestational mares who ingest Brassica plants, in particular Chorispora tenella, have had foals born with Congenital Hypothyroid Dysmaturity Syndrome. Symptoms include underbite, contracted tendons, uncharacteristic silky coat, and incompletely formed hock and carpal joints. Unfortunately, most of the foals do not survive. Additionally, isothiocyanates can cause renal dysfunction, liver and thyroid toxicity. In particular, isothiocyanates have a profound antithyroid effect by interfering with the synthesis of thyroid hormones. In this study, Chorispora tenella in the Fort Collins area was quantified for isothiocyanate content in 2010, 2016 and 2017. In 2010, there were three isothiocyanates present in this Brassica plant: allyl isothiocyanate, propyl isothiocyanate and butyl isothiocyanate. However, in the 2016 and 2017 plant samples there was only allyl isothiocyanate present. Lastly, HepG2 human hepatocarcinoma and K1 human thyroid carcinoma cells were used as cytotoxicity models for the liver and thyroid pathology seen after ingestion of plants from the Brassica family. Results show that HepG2 cells were more sensitive to the various isothiocyanates and to Chorispora tenella plant extracts than the K1 cell line. These findings show that exposure to isothiocyanates and Chorispora tenella may impact livestock health even at a subclinical level and provide baseline information for further studies investigating the molecular mechanism of cytotoxicity by isothiocyanates.